Inequity in Health Services Utilization in Economically Underdeveloped Regions of Northeast China - Zhang, Xin; Ning, Ning; Zhou, Hongguo; Shan, Linghan; Hao, Yanhua; Jiao, Mingli; Liang, Libo; Kang, Zheng; Li, Ye; Liu, Huan; Liu, Baohua; Wang, Kexin; et al. (Frontiers in Public Health, 2022)
Background: The Chinese health system has long been committed to eliminating inequalities in health services utilization. However, few studies have analyzed or measured health services utilization inequalities in economically underdeveloped regions in China. Methods: A total of 6,627 respondents from 3,000 households in Heilongjiang Province were extracted from the sixth National Health Services Survey. We measured horizontal inequity in both the two-week outpatient rate and annual inpatient rate, then identified the factors contributing to inequality. Results: The horizontal inequity indexes of the two-week outpatient and annual inpatient rates were 0.0586 and 0.1276, respectively. Household income, health status, urban/rural area, basic medical insurance, and commercial health insurance were the main factors affecting inequality in health services utilization in Heilongjiang Province. The contributions of household income to these two indices were 184.03% and 253.47%, respectively. Health status factors including suffering from chronic disease, limitations in daily activities, and poor self-rated health played positive roles in reducing inequality in these two indices. The contributions of place of residence to these two indices were 27.21% and -28.45%, respectively. UEBMI made a pro-rich contribution to these two indices, which were 56.25% and 81.48%, respectively. URRBMI, URBMI, NCMS, or other basic medical insurance made a pro-poor contribution to these two indices, which were -73.51% and -54.87%, respectively. Commercial health insurance made a pro-rich contribution to these two indices, which were 20.79% and 7.40%, respectively. Meanwhile, critical illness insurance made a slightly pro-poor contribution to these two indices. Conclusions: The findings showed that the “equal treatment in equal need” principle was not met in the healthcare utilization context in Heilongjiang Province, regardless of household income status. The government should make political changes to narrow the gap in the household economic status among citizens in economically underdeveloped regions, protect low-income citizens from the underuse of health services, and work to improve basic medical insurance, critical illness insurance, and social security systems.